The Straits Chinese contributions to Malaysian literary heritage: focus on Chinese stories translated into Baba Malay - Yoong, S.K.; Zainab, A.N. (2004)
The Chinese born in the Straits Settlements of Peninsula Malaya (Penang, Singapore, Malacca) are called Babas to distinguish them from those born in China. The Babas are rooted from three different races, Chinese, Malay and English and as such their lifestyles show a mixed blend of the Chinese, Malay and European cultures. Because of this cultural background, the Babas exhibited a unique cultural mix in the clothes they wear, their culinary skills, architectural styles, language and literature. The paper describes the characteristics of 68 Baba translated works published between 1889 and 1950; focusing on the publication trends between the period under study, the persons involved in the creative output, the publishers and printers involved, the contents of the translated works, the physical make-up of the works and the libraries where these works are held.